Towards a standardized bioinformatics infrastructure for N- and O-glycomics - Miguel A. Rojas-Macias (Nature Portfolio, 2019)
Glycomics is gaining momentum in basic, translational and clinical research. Here, the authors review current reporting standards and analysis tools for mass-spectrometry-based glycomics, and propose an e-infrastructure for standardized reporting and online deposition of glycomics data.